Controle da ingestão de água e sódio pelos mecanismos adrenérgicos do núcleo parabraquial lateral - Gasparini, Silvia (Universidade Federal de São Carlos, 2013)
The activation of α2-adrenoceptors with noradrenaline injected into the lateral parabrachial nucleus (LPBN) increases 1.8% NaCl intake in rats treated with the diuretic furosemide (FURO) combined with low dose of the angiotensin converting enzyme inhibitor captopril (CAP) subcutaneously (s.c.). In addition, noradrenaline injected into the LPBN increases arterial pressure and decreases water intake. In the present study, one of the objectives was to investigate the neural mechanisms activated by noradrenaline injected into the LPBN to produce pressor responses and the influence of the pressor response elicited by noradrenaline injected into the LPBN on FURO + CAP-induced water and 1.8% NaCl intake in rats. Male Holtzman rats with bilateral stainless steel guide-cannulas implanted into LPBN were used. Injections of noradrenaline (40 nmol/0.2 μl) into the LPBN increased FURO + CAP-induced 1.8% NaCl intake (12.2 ± 3.5, vs., saline: 4.2 ± 0.8 ml/180 min), reduced water intake in the first 90 min of the test (10.5 ± 0.9 vs., saline 7 ± 1.5 ml/90 min) and strongly increased arterial pressure (50 ± 7, vs. saline: 1 ± 1 mmHg). Results from the present work also showed that unilateral or bilateral noradrenaline injections (20 nmol/0.2 μl) into LPBL or in misplaced areas produced a pressure response (43.3 ± 6.4; 41 ± 7 respectively vs., saline: 2.5 ± 2.5 mmHg) and bradycardia (-51 ± 12; -82 ± 15 respectively vs., saline 6 ± 3.6 bpm) suggesting that noradrenaline pressure responses do not depend specifically on LPBN injections. The blockade of the α1 adrenoceptors with prazosin injected intraperitoneally (i.p.) abolished the pressor response (9 ± 4 vs., saline: 1 ± 1 mmHg) and increased water (17 ± 2 ml/180 min) and 1.8% NaCl intake (21.8 ± 3.8 vs., saline: 4.2 ± 0.8 ml/180), respectively in rats treated with FURO + CAP combined with noradrenaline injected into the LPBN. Although prazosin i.p. reduced the pressor response, the sympathetic blockade with hexamethonium combined with vasopressin receptor blockade increased the pressor response to noradrenaline injected into the LPBN (88 ± 30 vs., noradrenaline response before the blockade: 51 ± 4 mmHg), suggesting that these mechanisms are not involved in the pressor response. The results suggest that the pressor response reduces FURO + CAP-induced water intake and the facilitation of NaCl intake produced by noradrenaline injected into the LPBN. The present study also used licking microstructure analysis to draw conclusions about the effects of LPBN noradrenaline on orosensory and postingestive signals that modify intake. Male Sprague Dawley rats were used and treated with FURO+CAP before saline or noradrenaline was injected bilaterally into the LPBN. Noradrenaline (40 nmol/0.2μl) increased NaCl intake (8.3 ± 0.7 vs. saline 4 ± 0.4 ml) and the number of licks 15-30 into the test (439.1 ± 167.4 vs. saline 60.2 ± 35.2) and number of bursts (11.2 ± 5.8 vs. saline 1.9 ± 0.9) for NaCl in the same period. Pre-treatment with prazosin i.p. (1mg/kg of body weight) increased NaCl intake (13.4 ± 0.8 ml), the number of licks/bin between 45 and 90 min into the test (274.1± 91.4), the number of bursts/bin 30-60 min into the test (13.4 ± 9.0) and also by burst size 45 min into the test (41 ± 11 vs. saline 0 ± 0). Prazosin also further increased water intake (10.4 ± 0.6 vs. saline 7.1± 0.5) and the number of bursts between 30 and 60 min into the test (7.7 ± 2.8 vs. saline 0 ± 0). However, injections that did not reach the LPBN, though not produce an effect on total intake of sodium and water in animals treated with FURO + CAP, when combined with prazosin i.p. also produced similar effects on microstructural analysis of licking and caused an increase in the number of licks/bin and bursts/bin for NaCl, suggesting a non specificity of noradrenaline in the LPBN combined with prazosin i.p. on microstructural analysis of licks. In order to evaluate the effects of activation of α2-adrenergic LPBN receptors without the interference of the pressor response on postingestive and orosensory signals, lick analysis for water and 1.8% NaCl was measured in male Sprague Dawley rats that were treated with FURO + CAP and given vehicle or moxonidine injections into the LPBN. Bilateral injections of moxonidine (0.5 nmol/0.2 μl) into the LPBN increased FURO + CAP-induced total 1.8% NaCl intake (29.7 ± 7 vs. vehicle 4 ± 0.4 ml) and the number of licks/bin from 15 to 60 min (737 ± 267 vs. vehicle 0.0 ± 0.0 at 60 min). Moxonidine injections also increased the number of bursts/bin (36 ± 7 vs. vehicle 0 ± 0) number of licks/burst for 1.8% (26.5773 ± 8.1600 vs. vehicle 0 ± 0 at 60 minutes of the test). The results suggest that moxonidine into LPBN is affecting orosensory and postingestive signals for sodium intake. A stimulus that produces water intake and pressor response, but no hypertonic NaCl intake is the cholinergic stimulation with pilocarpine injected intraperitoneal (i.p.) or carbachol i.c.v. In this work it was also investigated whether the pressor response both pilocarpine i.p. as noradrenaline in the LPBN affects water and 1.8% NaCl intake induced by cholinergic activation. Further, it was investigated the effects moxonidine injections, an α2- adrenergic/imidazoline agonist, on water and 1.8% NaCl intake and the pressor response produced by pilocarpine i.p. Male Holtzman rats with bilateral stainless steel guide-cannulas implanted into LPBN were used. Pilocarpine (1 mg/kg) injected i.p. induced water intake (2.9 ± 0.3 ml/180 min), without affecting 0.3 M NaCl intake (0.5 ± 0.3 ml/180 min). Bilateral injections of noradrenaline (80 nmol/0.2 μl) into the LPBN combined with prazosin i.p. (1 mg/kg) increased pilocarpine i.p. induced water intake (6.3 ±1.7 ml/180 min) and 1.8% NaCl intake (14.7 ± 3.5 ml/180 min). LPBN noradrenaline injections combined with saline i.p. did not affect 1.8% NaCl (0.8 ±2.4 ml/180 min) and decreased water intake (0.8 ± 0.3 ml/180 min) induced by pilocarpine i.p. Prazosin i.p. did not modify 1.8% NaCl (4.8 ± 3.6 ml/180 min) or water intake (0.5 ± 0.3 ml/180 min) in rats treated with pilocarpine i.p. combined saline into the LPBN. Moreover, prazosin i.p. blocked the pressure response produced by noradrenaline injections into LPBN and also by pilocarpine i.p. (22 ± 4 vs., noradrenaline pressure response before saline i.p.: 60 ± 4 mmHg). In the present study, it was also observed that bilateral injections of moxonidine (0.5 nmol/0.2 μl) into the LPBN combined with pilocarpine i.p. induced 1.8% NaCl intake (14.1 ± 5.5 ml/180 min, vs. vehicle LPBN: 0.8 ± 0.5 ml/180 min) but did not change water intake (7.6 ± 3.1 ml/180 min, vs. vehicle LPBN 3.8 ± 0.7 ml/180 min) or pressure response produced by pilocarpine i.p. (30 ± 3 mmHg, vs., control: 28 ± 5 mmHg). The results suggest that strong cholinergic-induced sodium intake arises when the inhibitory mechanisms are deactivated with noradrenaline injected into the LPBN combined with the blockade of pressor responses with prazosin i.p. or moxonidine into LPBN. As pilocarpine i.p., i.c.v. injections of carbachol cause an increase in blood pressure, produce a dipsogenic response, but no intake of 1.8% NaCl. However, the present results show that noradrenaline injections into LPBN combined with prazosin i.p. did not alter water intake (8.1 ± 2.4 vs., i.p. saline LPBN 9.4 ± 4.8 ml/180 min), but produced an increase in 1.8% NaCl intake (8.2 ± 3.9 vs., saline LPBN 1.9 ± 0.8 ml/180 min) induced by carbachol (4 nmol/1 μ) i.c.v. Further, it was possible to observe that prazosin was able to reduce noradrenaline pressure response (15 ± 7 vs., noradrenaline pressure response before saline i.p.: 50 ± 9 mmHg) injected into LPBL but it did not change carbachol i.c.v. pressure response (28 ± 6 vs., vs., carbachol pressure response before saline i.p.: 25 ± 6 mmHg). The results suggests LPBN blockade and probably, pressure response associated with cholinergic activation induces sodium intake. Therefore, the present results suggest that besides inducing water intake, cholinergic stimuli also stimulate sodium intake when the inhibitory mechanisms are blocked by α2 adrenergic receptor activation in the LPBN. The activation of the α2 adrenergic receptor in the LPBN might remove, at least partially, baroreceptor and/or cardiopulmonary signals and orosensory or postingestive signals, such as signals from oral receptors, stomach, liver and intestine receptors, that might influence on water and sodium intake, which causes an increase in sodium intake. However, the inhibitory action of the increase in arterial pressure is still present, at least partially, after the blockade of the α2 adrenergic receptors in the LPBN, as suggested by the facilitation of water and sodium intake after the treatment with prazosin.
Keywords: Fisiologia; Apetite ao sódio; Noradrenalina; Pressão arterial; CIENCIAS BIOLOGICAS::FISIOLOGIA